Investigation of Rheological Characteristics of Powdered Activated Carbon Modified Bitumen for Use in Self-Healing Mechanism of Asphalt Concrete - Omid Jafari Ani; Gholamali Shafabakhsh; Seyed Mohamad Mirabdolazimi (Journal of Rehabilitation in Civil Engineering, 2024)
Asphalt pavement is used in road construction with the aim of withstanding loads and heavy traffic. Increasing axial loads and heavy vehicle traffic lead to failures, including rutting, thermal cracking, and fatigue cracking. These are the three most frequently observed distresses, especially in high-temperature regions that affect flexible pavement performance. Various studies over the years have investigated the causes of Hot mix asphalt failure and proposed a number of solutions to such failure problems. For upgrading the properties of asphalt mixtures against rutting, the asphalt bituminous exploited in the asphalt mixture was modified by employing Powdered Activated Carbon in this investigation. To apply the aging phenomenon, the specimens of control asphalt concrete and the specimens modified with Powdered Activated Carbon were held in the oven for 5 days at a temperature of 85 ℃. Bending beam rheometer (BBR) and dynamic shear rheometer (DSR) tests were performed on the specimens. The results revealed that the specimens containing Powdered Activated Carbon exhibited better performance against rutting. By adding 5% Powdered Activated Carbon, the high operating temperature of pure asphalt binder in the aged state has reached from 58 °C to 82 °C.